Analisis resepsi khalayak terhadap pemberitaan Covid-19 di klikdokter.com - Dwiputra, Krisna Octavianus (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
One of the health problems that will catch people's attention in 2020 is COVID-19. Various media also highlighted the problem because it was considered a dangerous thing. One of the media that participated in the news was a health media called Klikdokter.com. Klikdokter.com has been intensively reporting about COVID-19 since January 2020. The aim of the research is to see how the public perception about COVID-19 on Klikdokter.com. This research uses descriptive qualitative research. Methods of data collection using observation, interviews, and documentation. Meanwhile, informants were selected based on purposive sampling. The data analysis used Stuart Hall's Encoding-Decoding theory, which describes the three positions of the audience in constructing messages, namely dominant position, negotiation, and opposition. The results showed that the position of the audience in constructing messages from the news of COVID-19 on Klikdokter.com, the majority were in a negotiating position. This position means that the audience may misinterpret some parts of the message and quite understand what is conveyed by Klikdokter.com.Keywords: Covid-19; Reception; Reporting.